2018
DOI: 10.1111/cen.13741
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic approach to low‐renin hypertension

Abstract: Renin-angiotensin-aldosterone system (RAAS) plays a crucial role in maintaining water and electrolytes homoeostasis, and its deregulation contributes to the development of arterial hypertension. Since the historical description of the "classical" RAAS, a dramatic increase in our understanding of the molecular mechanisms underlying the development of both essential and secondary hypertension has occurred. Approximatively 25% of the patients affected by arterial hypertension display low-renin levels, a definitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
7

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 115 publications
(249 reference statements)
0
12
0
7
Order By: Relevance
“…Ultimately, a low-renin state, which compensates for the relative tendency to retain sodium, ensues [50]. Low-renin hypertension is a frequent cause of hypertension, with a prevalence of 20%–30%, and higher in African Americans [51,52,53]. One study demonstrated lower levels of plasma renin activity and aldosterone in normotensive African Americans across all ages, with BP positively correlating with plasma aldosterone, an effect that increased as plasma renin activity decreased [48].…”
Section: Hypertension In African Americans: Clinical Differences Amentioning
confidence: 99%
“…Ultimately, a low-renin state, which compensates for the relative tendency to retain sodium, ensues [50]. Low-renin hypertension is a frequent cause of hypertension, with a prevalence of 20%–30%, and higher in African Americans [51,52,53]. One study demonstrated lower levels of plasma renin activity and aldosterone in normotensive African Americans across all ages, with BP positively correlating with plasma aldosterone, an effect that increased as plasma renin activity decreased [48].…”
Section: Hypertension In African Americans: Clinical Differences Amentioning
confidence: 99%
“…В связи с этим для выявления первичного альдостеронизма помимо измерения концентраций альдостерона в плазме крови стали использоваться некоторые динамические тесты, призванные доказать наличие и автономность гиперсекреции альдостерона. Оказалось, что выраженность отклонений в концентрациях ренина и альдостерона необходимо оценивать не только по абсолютному их количеству, но и по соотношению альдостерон/ренин (Funder et al, 2016;Monticone et al, 2018b). Величина этого коэффициента, на основании которого можно с определенной уверенностью говорить о возможном наличии у пациента альдостеронизма, к сожалению, четко не определена, тем не менее считается, что она должна превышать 30, если уровень ренина оценивается по его способности синтезировать ангиотензинI (ng/ml/h), и этот коэффициент должен быть выше 3.7, если измеряется не активность, а концентрация ренина в плазме (mU/L).…”
Section: первичный альдостеронизм и соотношение альдостерон/ренинunclassified
“…Si bien es materia de controversia, se acepta como renina suprimida a: Renina directa (DRC) < 6-10 uUI/mL o una actividad de renina en plasma (ARP) < 0,8-1,0 ng/mL/h dependiendo del método utilizado y la ingesta de sodio del paciente 5 . Puede estimarse ARP dividiendo DRC por un factor de 8,2 14 .…”
Section: Definición De La Hta Hiporreninémicaunclassified
“…La hipertensión hiporreninémica (HTAH) agrupa a un sinnúmero de condiciones cuyo mecanismo fisiopatológico de elevación de la presión arterial es la activación del receptor mineralocorticoide (MR) con la consiguiente activación del canal epitelial de sodio en el nefrón distal (ENaC), que aumenta directamente la reabsorción de sodio y secundariamente agua por las vías que le son propias. Esto, en definitiva, es censado por la mácula densa, disminuyendo los niveles de renina 4,5 .…”
unclassified